Analysis of the Relationship between Attitude and Competence and Quality of Poned Services at the Tapa Health Center, Bone Bolango Regency - Mentari N. Tuna; Herlina Jusuf; Yasir Mokodompis (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (MMR) are important indicators in assessing people's welfare. In Indonesia, AKI and AKB are still high, including in Gorontalo Province. The Tapa Health Center faces challenges in PONED services, which are not yet fully effective. This study aims to analyze the relationship between the attitude and competence of health workers and the quality of PONED services at the Tapa Health Center. The method used was an analytical survey with a Cross Sectional design, which examined the relationship between risk factors (attitudes and competencies) and consequences (quality of service) simultaneously. This research was carried out at the Tapa Health Center, Bone Bolango Regency, in January-March 2025. The results showed that there was a significant relationship between the attitude of health workers and the quality of PONED services with a P-value of 0.070, as well as between the competence of health workers and the quality of PONED services with a P-value of 0.035. In conclusion, the attitude and competence of health workers affect the quality of PONED services. Therefore, it is recommended that the Tapa Health Center improve competency training for health workers, provide better managerial support, conduct periodic evaluations, and involve health workers in decision-making to improve the quality of PUNE services.